Synthesis of molecularly imprinted polymer by precipitation polymerization for the removal of ametryn - Rachel Marcella, Roland; Showkat Ahmad, Bhawani; Mohamad Nasir, Mohamad Ibrahim (BioMed Central Ltd, 2023)
Ametryn (AME) is a triazine herbicide which is mainly used to kill unwanted herbs in crops. Despite its importance in agriculture, the usage of AME also poses a risk to humans and the ecosystem due to its toxicity. Hence, it is important to develop a method for the efective removal of AME from various water sources which is in the form of molecular imprinting polymer (MIP). In this study, MIP of AME was synthesized via precipitation polymerization using AME as the template molecule with three diferent functional monomers including methacrylic acid (MAA), acrylamide (AAm) and 2-vinylpyridine (2VP). The three diferent synthesized polymers namely MIP (MAA), MIP (AAm) and MIP (2VP) were characterized using Fourier Infra-red spectroscopy (FTIR) and Field Emission Electron Microscopy (FESEM). Then, the batch binding study was carried out using all three MIPs in which MIP (MAA) attained the highest rebinding efciency (93.73%) among the synthesized polymers. The Energy-Dispersive X-ray spectroscopy (EDX) analysis, Brunauer–Emmett–Teller (BET) analysis and thermogravimetric analysis (TGA) were also conducted on the selected MIP (MAA). Adsorption studies including initial concentration, pH and polymer dosage were also conducted on MIP (MAA). In this study, the highest adsorption efciency was attained at the optimum condition of 6 ppm of AME solution at pH 7 with 0.1 g of MIP (MAA). MIP (MAA) was successfully applied to remove AME from spiked distilled water, tap water and river water samples with removal efciencies of 95.01%, 90.24% and 88.37%, respectively